Improving groundwater storage change estimates using time-lapse gravimetry with Gravi4GW. (April 2022) - Halloran, Landon J.S.
Abstract: Time-lapse gravimetry (repeat microgravity measurement) is a powerful tool for monitoring temporal mass distribution variations, including seasonal and long-term groundwater storage changes (GWSC). This geophysical method for measuring changes in gravity (Δ g ) is potentially applicable to any groundwater system. Here, I present Gravi4GW, a Python tool for the site-adapted calculation of β, the conversion factor between Δ g and GWSC (also known as "topographic admittance"). Alpine catchments, in particular, are ideal target sites as they are highly sensitive to climate variations and can experience significant GWSC, while often lacking groundwater monitoring infrastructure. Therefore, to illustrate the usage of Gravi4GW, I investigate a detailed example of an alpine catchment and examine spatial variations and the effects of depth assumptions. This novel and accessible tool is designed to be useful in both the planning and data processing stages of time-lapse gravimetric field studies. Highlights: Gravi4GW converts between Δ g and groundwater storage changes. Conversion factor β can also be used to target field measurements. The Python software tool can use DEM or groundwater elevation data. Use of Gravi4GW in an alpine catchment demonstrated. Effects of topography and slope on β investigated.